Hi everyone,

I have a question according to sets.

Imagine the set n, the set i and the subset x(n,i). Is there an easy way to for the equation x(n,i+1) = x(n^-1,i)?

Here is what I mean in a more detailed way:

set n /1*3/*

i /120/

x(n,i);

So x got 3 values. Let’s say they get some values in the time step 8:

x(1,8) = 2

x(2,8) = 5

x(3,8) = 16

No I want to attach the values in the next timestep to:

x(1,9) = 16

x(2,9) = 5

x(3,9) = 2

The change should be dependent on some conditions, but i think it is easy to do this with binary variables.

I hope you understand, what I want to do. Thanks in advance!

Cheers

What does n^-1 means in this :

x(n,i+1) = x(n^-1,i)

?

Are there always three members of n and the last and the first “exchange” each other sequentially ? ie:

x(1,1)=1

x(2,1)=2

x(3,1)=3

x(1,2)=3

x(2,2)=2

x(3,2)=1

x(1,3)=1

x(2,2)=2

x(3,3)=3

Are valid values ?

Hi cladelpiano,

n^-1 should mean, that it is the inverted value. The equation should express, when n is 3:

x(1,i+1) = x(3,i)

x(2,i+1) = x(2,i)

x(3,i+1) = x(1,i)

n is not supposed to have 3 members all the time. It represents the number of nodes for a system, so it should be flexible.

i represents the time. The values should not exchange every timestep, but dependent on the values of the binary variables chg(i+1) and dis(i+1).

Does that answer your question?

Cheers

ehh… no ?

n^-1 should mean, that it is the inverted value.

What do you mean by “inverted” ? Why is inverted(1)=3 and inverted(3)=1 ?

Is it exchanging the last and first element ? For example for n= 4

x(1,i+1) = x(4,i)

x(2,i+1) = x(2,i)

x(3,i+1) = x(3,i)

x(4,i+1) = x(1,i)